Relationship Between Job Embeddedness and Employee Work Engagement with Leader-Member Exchange and Person–Organization Fit as Predictors: Evidence from North Sumatra - Efendi Efendi; Elly Romy; Ramesh Krishnan; Acai Sudirman (Jurnal Organisasi dan Manajemen, 2024)
Purpose – This research aimed to analyze relationship between leader-member exchange, person-organization fit, and perceived organizational support on employee work engagement. Methodology – The samples comprised 200 civil servants in North Sumatra Province. Data were collected from an online survey using a 5-point Likert scale following a non-probability with a purposive sampling method. Data obtained were analyzed using Smart-PLS through Structural Equation Modeling (SEM). Findings – The results showed that job embeddedness, person-organization fit, and perceived organizational support significantly affected employee work engagement, while leader-member exchange did not have a significant effect. Originality – This research contributed significantly to the literature on work engagement of civil servants in North Sumatra Province. Although the literature on work engagement has developed significantly, research that specifically pays attention to the population of civil servants in this area is limited. The results provide a deeper understanding of the factors influencing work engagement, offering insights into the unique local context and specific characteristics that may affect relationship between the variables.